Reward and Punishment as Learning Motivation at Mts.S Al-Wasliyah Deli Serdang Regency - Anri Naldi; Lahmuddin Lubis; Nurmawati Nurmawati (SYAMIL: Journal of Islamic Education, 2024)
This study aims to analyze the implementation of reward and punishment as a learning motivation system. This research is a qualitativeresearch with a phenomenological approach. The sampling technique used is purposive sampling. The data collection technique was carried out using observation, interviews and document studies. Data analysis uses data reduction, data categorization, synthesis, and ends by compiling a working hypothesis. The results of the reward and punishment research as learning motivation carried out are twofold: First, a policy system is carried out, which is in accordance with the policies and regulations in the Madrasah. Second, a teacher policy system is carried out in the learning process. The policy system regulates discipline carried out by madrasas in general, applies to all madrasah residents, both educators, educators, and students. Meanwhile, the teacher policy system is carried out based on the situation of students in the classroom, both for classroom teachers and teachers in the field of study in achieving students' cognitive, affective and psychomotor abilities. The conclusion of this study is the implementation of reward and punishment as a learning motivation system, namely a policy system based on madrasah regulations and a teacher policy system of teacher authority in increasing students' learning motivation both in terms of cognitive, affective and psychomotor.